2006
DOI: 10.1124/mol.106.026815
|View full text |Cite
|
Sign up to set email alerts
|

Role in the Selectivity of Neonicotinoids of Insect-Specific Basic Residues in Loop D of the Nicotinic Acetylcholine Receptor Agonist Binding Site

Abstract: The insecticide imidacloprid and structurally related neonicotinoids act selectively on insect nicotinic acetylcholine receptors (nAChRs). To investigate the mechanism of neonicotinoid selectivity, we have examined the effects of mutations to basic amino acid residues in loop D of the nAChR acetylcholine (ACh) binding site on the interactions with imidacloprid. The receptors investigated are the recombinant chicken ␣4␤2 nAChR and Drosophila melanogaster D␣2/chicken ␤2 hybrid nAChR expressed in Xenopus laevis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 45 publications
3
121
0
Order By: Relevance
“…15) Site-directed mutagenesis has recognized several amino acids which potentially modulate neonicotinoid agonist action. 16,17) Photoaffinity labeling is an alternative and direct approach for structural investigation of the target. Azidochloropyridinyl neonicotinoids are candidate photoaffinity probes.…”
Section: Photoaffinity Labeling Of Achbpmentioning
confidence: 99%
“…15) Site-directed mutagenesis has recognized several amino acids which potentially modulate neonicotinoid agonist action. 16,17) Photoaffinity labeling is an alternative and direct approach for structural investigation of the target. Azidochloropyridinyl neonicotinoids are candidate photoaffinity probes.…”
Section: Photoaffinity Labeling Of Achbpmentioning
confidence: 99%
“…16,17) The discovery and subsequent crystal structure analyses of structural and functional surrogates of the agonist binding domain of nAChRs have been of great help in promoting understanding about the ligand recognition properties of the binding site at atomic resolution, 18,19) and knowledge of the neonicotinoid binding site of insect nAChRs has remarkably advanced. [20][21][22][23][24][25] In comparisons between ligand affinities for AChBPs from three molluskan species and those for Pa-nAChRs, it was observed that the addition of a hydroxyl group to the para-position of BA to give 6 led to 25-and 10-fold increases in affinity for LsAChBP and Pa-nAChRs, respectively, whereas the influence of this substitution was small for Aplysia californica (Ac)-and Bulinus truncates (Bt)-AChBP, indicating the similarity of PanAChRs to Ls-AChBP. 13) Pa-nAChRs are also similar to LsAChBP in terms of the markedly low affinity of 5 compared to 6; however, Pa-nAChRs are similar to Bt-AChBP in the effect of the ortho-methoxy group.…”
Section: Resultsmentioning
confidence: 99%
“…The E79 residue of the chicken β2 subunit may suppress interactions between the nitro group of neonicotinoids and Arg 77 through the negative electrostatic forces of Glu79. 10) The T77R and T77R+E79V mutations did not significantly affect the pEC 50 and I max values for the natural agonist ACh (Table 3), compared with those of the wild-type Dα2β2 nAChR (WT). The pEC 50 values of acetamiprid and imidacloprid for wild-type Dα2β2 nAChR were 5.26±0.09 and 5.61±0.06, respectively.…”
Section: Nachr and Neonicotinoid Resistance Of Cotton Aphid (Aphis Gomentioning
confidence: 99%
“…This method is suitable for the expression and analysis of receptors of a wide range of biological strains, especially for the analysis of variants. 10) Another method is the patch clamp method; this enables various measurements, is particularly applicable to the nerve cells of insects, and enables evaluation of the effects or activities of a compound on the expression of receptors in an insect's body. The third method is the automatic patch clamp method.…”
Section: Introductionmentioning
confidence: 99%